Eastern Elements in Cathar Doctrines – an Argument for the Traditional Interpretation of Catharism - Czarnecki, Piotr (Studia Ceranea, 2024)
At present we can observe intense attempts at overthrowing all the claims concerning Catharism that had been formulated by the scholars of the 20th century, based on careful analysis of the vast source material. So called “traditional interpretation”, assuming strong influence of the Eastern dualist heresies (Bogomilism and Paulicianism) on Catharism is currently rejected by scholars such as M. G. Pegg, J.-L. Biget and R. I. Moore as outdated and not compatible with the latest research. For the construction of this false image of Catharism Pegg blames Religionsgeschichte Schule and their comparative method, which according to him is built on the assumption that “if two ideas look alike to the historian, there must be a link between them”, but in this radical criticism, he seems to ignore the fact that comparison of the Cathar and Bogomil doctrine is justified by many sources, which confirm historical relations between the adherent of these heresies. What should be underlined, not only the current deconstructionist conception, represented by the above-mentioned scholars, but all the interpretations rejecting Eastern origins of Cathar doctrines, were constructed without the analysis of the Eastern sources. Considering this, the aim of this article is to analyse various specific Cathar doctrinal conceptions, which do not have analogies in the ancient heresies, with the doctrines of the Eastern dualists (mainly Bogomils but also Paulicians), known from the Eastern sources – both polemical and written (or used) by the heretics themselves. Such comparative analysis can verify the claims of the adherents of the “new paradigm”, according to which dualist Cathar doctrine was constructed by Catholics, basing on the ancient anti-heretical scriptures, mainly anti-Manichaean writings of St. Augustine.